ASSOCIATION BETWEEN PREVENTIVE BEHAVIOUR ON COLORECTAL CANCER AND HEALTH LITERACY AMONG THE ADULT POPULATION IN SARAWAK, MALAYSIA - Jores, Drend; Abdullah, Abdul Rahim; Rahman, Md Mizanur (Malaysian Journal of Public Health Medicine, 2021)
Health literacy has shown to have some influence in preventive behaviour, including on colorectal cancer. Such a relationship, however, is not well established in Malaysia, particularly Sarawak. This study is aimed to estimate the level of health literacy and preventive practice against colorectal cancer and factors associated with it. This was a cross-sectional study conducted in Sarawak, among adults aged 50 years and above. Data was collected by face to face interviews using a validated questionnaire. Descriptive statistics were used to determine the health literacy and preventive behaviour on colorectal cancer. Multiple linear regression was used to determine the factors associated with preventive behaviour on colorectal cancer and also to examine its relationship with health literacy. A p-value of ?0.05 was considered as statistically significant. A total of 829 respondents were included in the analysis. Mean age (standard deviation) of the respondents was 55.78 (5.01) years. A large proportion had an educational background of upper secondary school and above (41%) and from Iban ethnicity (32.4%). Only 1.1% of them had a family history of colorectal cancer. Multiple linear regression analysis revealed that gender (p<0.01), ethnicity (p<0.05), functional health literacy (p<0.05), and knowledge on colorectal cancer (p<0.05) appeared to be significant predictors for preventive behaviour on colorectal cancer. Health literacy has a positive effect on preventive behaviour on colorectal cancer. The findings assist in designing and developing targeted informational campaigns to promote preventive behaviour, particularly among low health literate group.